ANALISIS KENDALA GURU DALAM PERENCANAAN PEMBELAJARAN DARING DI SDN 48 CAKRANEGARA - Agus Sopyan Ronadi; Lalu Hamdian Affandi; Heri Setiawan (Program Studi PGSD, FKIP, Universitas Mataram, 2022)
This study aims to identify teacher constraints in online learning planningt, the subjects in this study were all 16 teachers or educators at SDN 48 Cakranegara. This research uses a sequential exploratory mixed methods approach. Sources of data to be used include primary data and secondary data. Primary data obtained by researchers directly through a questionnaire (questionnaire) and interviews. Sources of secondary data obtained through the results of a literature study. The results showed that there were two obstacles faced by teachers at SDN 48 Cakranegara Mataram City in planning bold lessons with the percentage of results 76. 25% and 77.50% being the lowest scores. The obstacles faced by teachers at SDN 48 Cakranegara Mataram City in planning bold learning are the lack of knowledge and understanding of teachers regarding bold RPP and lack of initiative and creativity as well as teacher activity in developing interesting learning methods independently. As a teaching and learning method that has just been applied online learning or distance learning , of course as a teacher or educator it is expected to increase understanding and abilities related to online learning and add insight into technology and the internet, in order to optimize teacing and learning activities, especially online learning Keywords: Teacher Constraints, Lesson Planning, Online learning